Stationary heat conduction in laminates with non-uniform distribution of laminas = Stacjonarne przewodnictwo ciepła w laminatach o nierównomiernym rozmieszczeniu warstw - Jędrysiak, Jarosław (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
In this paper it is analysed a stationary heat conduction in laminates made of two materials non-periodically distributed as microlaminas along one direction. It is assumed that this laminate has a functionally (transversally) graded macrostructure along this direction. Some effects of the microstructure in a distribution of a temperature are investigated using the tolerance modelling.
Keywords: laminaty; poprzeczna gradacja struktury; przewodnictwo cieplne; laminates; transversally graded structure; nonhomogeneous distribution of laminas; heat conduction